Gender-based depression trajectories following heart disease onset: significant predictors and health outcomes. (3rd April 2022) - Kong, Dexia; Lu, Peiyi; Solomon, Phyllis; Shelley, Mack
Abstract: Background: Using a nationally representative sample of U.S. older adults (50+), this study investigates gender-based depression trajectories following heart disease onset and associated risk of disability and mortality over an 8-year period. Method: Six waves of longitudinal data from the Health and Retirement Study (2006–2016) were used ( n = 1787). Heart disease onset was defined as self-reporting no heart disease at baseline but reporting a positive diagnosis in a subsequent wave. Growth Mixture Modelling identified depression trajectories. Multinomial logistic regression models determined significant predictors of depression trajectories. Cox proportional-hazards models examined the associated disability and mortality risks. Results: Three distinct depression trajectories were identified, including persistent minimal depression (men: 68.65%; women: 60.17%), moderate depression (women: 29.70%; men: 17.97%), and chronic depression (women: 10.12%) or emerging depression (men: 13.38%). Younger age and depression status at baseline were associated with women's chronic depression and men's emerging depression. Chronic/emerging and moderate depression were associated with higher disability risks than was minimal depression among both women and men (hazard ratios [HR] ranged from 2.12 to 3.92, p < 0.001). Only men's emerging depression was linked to higher mortality risk compared to minimal depression (HR = 2.03, p < 0.001). Conclusion: Longitudinal course of depression following onset of heart disease is heterogeneous in later life. Unfavorable depression trajectories (i.e. moderate, chronic, and emerging) were associated with higher disability risk compared to the minimal depression trajectory. Study findings characterize risk stratification regarding depression after heart disease onset, which can inform the development of interventions to improve health outcomes among older adults with heart conditions.